ANALISIS PENGARUH EKUITAS MEREK TERHADAP RETENSI PELANGGAN UNTUK PRODUK INDIHOME DI PT. TELKOM INDONESIA WITEL MEDAN - Fina Fina; Opim Salim; Sugiharto Pujangkoro (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Parameters of LIS (Line in Service) customers and sales Indihome the end of 2015 showed symptoms that customers are reluctant to migrate existing services to Indihome. One of the factors that affect customer retention is the brand equity. This study aims to determine the significance of brand equity influence on customer retention. The results showed that the overall contribution of the influence of the independent variables, namely:differentiation, relevance, esteem, and knowledge, are air-alike on the migratory behavior (customer retention) to Indihome was 60.3%. The remainder of the contribution is determined by factors other than the so-called predictor in this study. The study thus shows that both the variable relevance, differentiation, knowledge, and awards have significantlyinfluenced the migration service, with variable relevance seba-gai factors that most influence on customer retention. In connection with the results and discussion of this study, it is expected that their further studies to investigate other indicators (39.7%) affecting existing customers willing to migrate to Indihome. Based on the results of research of thisaddition, the company management needs to formulate strategic policies related variables relevance, differentiation, knowledge, and awards to increase the number of existing customers who are willing to migrate to Indihome.Keywords: Ekuitas Merek, Telkom, Pelanggan.